Econometric Analysis of Inflation Dynamics in Digital Payment Ecosystems in Emerging Markets - Syafi’i, Akhmad (Journal of Applied Econometric, 2025)
Inflation in emerging markets is becoming a serious challenge in the face of rapid digital transformation, especially with the increasing use of digital payments changing consumption patterns and financial transactions. Within this ecosystem, digital payment services such as mobile banking and e-wallets open up wider economic access, but they also raise concerns about their impact on inflation stability, particularly in countries with macroeconomic vulnerabilities. This study aims to analyze the influence of the digital payment ecosystem on inflation dynamics in emerging markets, using dynamic panel econometric analysis with data samples from 20 developing countries in the period 2015–2023. Key variables include digital payment penetration rates, annual inflation, as well as control indicators such as GDP growth, unemployment rates, and interest rates. The results show that the adoption of digital payments has a significant impact on inflation dynamics, where the increased use of digital payments tends to accelerate the inflation response to changes in demand and prices. In addition, in countries with immature financial systems, the high penetration of digital payments amplifies inflationary volatility, demonstrating the need for adaptive monetary supervision. These findings provide insight for policymakers on the importance of balancing digital financial innovation with monetary policy to maintain economic stability